A hipertrofia da extraconcursalidade no agronegócio: bases para a construção de um microssistema de insolvência setorial - Tironi, Fábio Aparecido (2025)
This thesis offers a critical analysis of the insolvency regime applicable to rural producers in Brazil, with a focus on the amendments introduced by Law No. 14,112/2020 to Law No. 11,101/2005. It investigates the structural paradox of the reform, which, while consolidating the eligibility of rural producers for judicial reorganization (recuperação judicial), significantly expanded the hypotheses of priority treatment outside the insolvency estate (extraconcursalidade) specifically for the sector. The work examines the tension between this new normative architecture and the principle of preservation of the enterprise (art. 47 of the Brazilian Business Reorganization and Insolvency Act – LREF), starting from the premise of the autonomy of Agribusiness Law as a legal microsystem. Using a qualitative methodology with a deductive, critical and comparative approach (United States, Canada, France, Germany, Argentina and Uruguay), based on bibliographic, documentary and case-law analysis, the thesis explores the historical evolution of the sector, its financing structure and the current insolvency framework. The findings confirm the central hypothesis that the “hypertrophy of extraconcursality” – encompassing essential instruments such as the physical Rural Product Note (cédula de produto rural – CPR), barter operations, regulated rural credit, cooperative acts and the controversial ring-fencing of the natural person’s assets – empties the effectiveness of the reorganization regime by withdrawing a substantial share of agricultural indebtedness from the collective creditors’ proceedings (concurso de credores). The thesis also criticizes the inadequacy of the restrictive case-law concept of “essential capital goods”, which, by requiring corporeality and non-consumable nature, disregards the functional essentiality of inputs, intangible assets and the crop itself for agricultural activity. It is demonstrated that the Brazilian model (“general and subsumptive”) is misaligned with international trends towards specialization (“specialized and protective” or “preventive and hybrid”). The thesis concludes that the current regime is structurally dysfunctional and proposes, de lege lata and de lege ferenda, the foundations for constructing a sectoral insolvency microsystem for agribusiness, grounded in adaptive universalism, prevention (specialized pre-insolvency mediation), adaptability to production cycles and specific financing mechanisms (DIP Safra).